TESTING MOTOR SKILLS WITH CHILDREN AGED 4 AND 5 YEARS IN SPORT SCHOOL "SPORTOMANIJA" - Vladimir Milošević; Adam Petrović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Children aged 4 and 5 have great motor potential. Testing certain motor skills and measuring morphological characteristics are important steps in examining sport development of children. The subject of this paper is assessing motor skills and measuring morphological characteristics of students of sport school Sportomanija in Belgrade. The sample was made up of 16 male examinees aged 4 and 5. The battery of motor tests was composed of the following : deep reach (standing position), standing long jump, 20 metres running, 4x5 metres running, lying into sitting position in 20 seconds. Statistical analysis of results meant correlating results of motor tests and anthropometric measurment. The results show a statistically relevant negative correlation between body mass index (BMI) and long jump results (r=-0,55, p<0,05). On the other hand, there is a high positive correlation (over r=0,70, p<0,05 ) between the results of motor tests: standing long jump, 20 metres running, 4x5 metres running, lying-sit in 20 seconds. These resultes are in the accordance with the similarity in the ways muscle strength is manifested under different conditions. Considering the correlation between these results provides the basis for testing the nature of this conection. Examining the connection between the anthropometric and motor scope during a targeted influence on a child's body in sport school Sportomanija allows for gaining insight into some of the characteristics of the examinee's age. Acquaitance with examinee's model characteristics as well as structure of motor skills and longterm examining of anthropometric and motor scope are the basis of plan and action of the experts working with children and the young.